Ethnic representation within virtual reality: a co-design study in a forensic youth care setting - Renée E. Klein Schaarsberg; Levi van Dam; Guy A. M. Widdershoven; Ramón J. L. Lindauer; Arne Popma (BMC Digital Health, 2024)
Abstract Background Virtual reality (VR) is one of the most cutting-edge digital technologies currently used to extend and adapt mental health interventions. When designing therapeutic VR-applications, bias related to representational and behavioral features can be introduced. Specific bias, that could result from ethnic stereotyping, should be averted. However, structured debates and clear guidelines on how to deal with such bias are lacking. Objective In the current paper we describe our iterative, co-design process to develop an augmented version of a 360-degree VR-video that is used in the Street Temptations intervention. In this intervention, aimed at adolescents with disruptive behavior problems, the VR-video provides adolescents with an emotionally engaging situation and forms the basis of Street Temptations’ perspective-taking exercises. By presenting a detailed example of our VR developmental process, specifically focusing on ethnic representation in this virtual environment and related ethical aspects, we aim to positively contribute to the creation of ethically sound therapeutic VR-applications. Method We adopted an experience-based co-design approach. The process started by assembling professionals’ experiences with the original VR-video. Following, we conducted four co-design groups with adolescents, young adults, and professionals within the forensic youth care system, as experiential experts, to collaboratively develop an enhanced VR-scenario for the Street Temptations intervention. In total, ten adolescents, four young adults and four professionals participated. The co-design groups were alternated with sessions with a screenwriter, to reflect on the results of the co-design groups. In this way, we enabled continuous feedback on and design of the ameliorated scenario and let development and data collection reinforce each other. Results The most important adjustments that were brought forward included explicit incorporation of diversity, establishing a clear storyline for the scenario, keeping the content close to reality, casting actors in a way to avoid obvious stigmatization, and using only names for the characters that are commonly used across different cultural and ethnic backgrounds. Discussion By presenting our developmental process, we give a detailed example of how to reflectively develop ethically sound therapeutic VR-content within a forensic youth care setting. We demonstrated that including stakeholders can help in preventing socially irresponsible and conceivably hurtful stereotypes. By describing the process in detail, we hope to contribute to the responsible use of technology within mental health care.